Evolution of Highly Pathogenic Avian Influenza A(H5N1) Virus in Poultry, Togo, 2018 - Fusade-Boyer, Maxime (Emerg Infect Dis, 2019)
In 2015, highly pathogenic avian influenza A(H5N1) viruses reemerged in poultry in West Africa. We describe the introduction of a reassortant clade 2.3.2.1c virus into Togo in April 2018. Our findings signal further local spread and evolution of these viruses, which could affect animal and human health.